Elevated CO 2 Increases the Canopy Temperature of Mature Quercus robur (Pedunculate Oak) - William Hagan Brown; Emanuel Gloor; Ralph Fyfe; A. Rob MacKenzie; Nicholas J. Harper; Peter Ganderton; Kris Hart; Giulio Curioni; Susan Quick; Scott J. Davidson; Emily Yetton; Jen L. Diehl; et al. (Global Change Biology, 2025)
The canopy thermal response of natural forests to elevated CO 2 (eCO 2 ) is an understudied biophysical feedback in the global climate system. We investigated the effects of eCO 2 (150 μmol mol −1 above ambient) on canopy temperature ( T can ) dynamics of mature (> 175 years) Quercus robur (oak) at the Birmingham Institute for Forest Research Free Air CO 2 Enrichment (BIFoR‐FACE) facility in Staffordshire, England, during the growing seasons of 2021, 2022 and 2023. We employed long‐term, high‐frequency thermal infrared (TIR) imaging to measure T can . Our results show that daily maximum oak T can under eCO 2 was, on average, approximately 1.3°C higher than under ambient (aCO 2 ) conditions (21.5°C ± 4.4°C for aCO 2 vs. 22.8°C ± 5.2°C for eCO 2 oaks). Moreover, daily maximum T can –air temperature ( T air ) differences were significantly higher under eCO 2 , resulting from more frequent extreme temperature excursions. These differences appear primarily to be driven by reduced stomatal conductance under eCO 2 , which limits transpirational cooling and alters the surface energy balance. This effect was evident in the different relationship between T can – T air and vapour pressure deficit (VPD) for eCO 2 compared to aCO 2 , showing a reduction in transpirational cooling under high VPD. Also, CO 2 ‐induced leaf structural and anatomical modifications, such as increased leaf mass per area, may have enhanced solar radiation absorption, thereby enabling greater canopy warming under high radiation conditions. Thus, eCO 2 could likely cause a reduction in leaf transpiration in oaks, reducing its contribution to processes such as humidification of the lower atmosphere and precipitation in local and regional climates. Our findings highlight how high CO 2 conditions may intensify thermal stress in temperate forests, influencing water and carbon cycles and potentially impacting forest resilience. Furthermore, T can will be essential for refining global Earth system models, which often use T air as a proxy for T can , despite the latter's direct influence on carbon and hydrological cycles.

Microclimate, an important part of ecology and biogeography - Julia Kemppinen; Jonas J. Lembrechts; Koenraad Van Meerbeek; Jofre Carnicer; Nathalie Isabelle Chardon; Paul Kardol; Jonathan Lenoir; Daijun Liu; Ilya Maclean; Jan Pergl; Patrick Saccone; Rebecca A. Senior; et al. (Global Ecology and Biogeography, 2024)
Brief introduction: What are microclimates and why are they important? Microclimate science has developed into a global discipline. Microclimate science is increasingly used to understand and mitigate climate and biodiversity shifts. Here, we provide an overview of the current status of microclimate ecology and biogeography in terrestrial ecosystems, and where this field is heading next. Microclimate investigations in ecology and biogeography We highlight the latest research on interactions between microclimates and organisms, including how microclimates influence individuals, and through them populations, communities and entire ecosystems and their processes. We also briefly discuss recent research on how organisms shape microclimates from the tropics to the poles. Microclimate applications in ecosystem management Microclimates are also important in ecosystem management under climate change. We showcase new research in microclimate management with examples from biodiversity conservation, forestry and urban ecology. We discuss the importance of microrefugia in conservation and how to promote microclimate heterogeneity. Methods for microclimate science We showcase the recent advances in data acquisition, such as novel field sensors and remote sensing methods. We discuss microclimate modelling, mapping and data processing, including accessibility of modelling tools, advantages of mechanistic and statistical modelling and solutions for computational challenges that have pushed the state‐of‐the‐art of the field. What's next? We identify major knowledge gaps that need to be filled for further advancing microclimate investigations, applications and methods. These gaps include spatiotemporal scaling of microclimate data, mismatches between macroclimate and microclimate in predicting responses of organisms to climate change, and the need for more evidence on the outcomes of microclimate management.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

The population structure and recent colonization history of O regon threespine stickleback determined using restriction‐site associated DNA ‐sequencing - Julian Catchen; Susan Bassham; Taylor Wilson; Mark Currey; Conor O'Brien; Quick Yeates; William A. Cresko (Molecular Ecology, 2013)
Understanding how genetic variation is partitioned across genomes within and among populations is a fundamental problem in ecological and evolutionary genetics. To address this problem, we studied the threespine stickleback fish, which has repeatedly undergone parallel phenotypic and genetic differentiation when oceanic fish have invaded freshwater habitats. While significant evolutionary genetic research has been performed using stickleback from geographic regions that have been deglaciated in the last 20 000 years, less research has focused on freshwater populations that predate the last glacial maximum. We performed restriction‐site associated DNA ‐sequencing ( RAD ‐seq) based population genomic analyses on stickleback from across O regon, which was not glaciated during the last maximum. We sampled stickleback from coastal, Willamette Basin and central O regon sites, analysed their genetic diversity using RAD ‐seq, performed structure analyses, reconstructed their phylogeographic history and tested the hypothesis of recent stickleback introduction into central O regon, where incidence of this species was only recently documented. Our results showed a clear phylogeographic break between coastal and inland populations, with oceanic populations exhibiting the lowest levels of divergence from one another. Willamette Basin and central Oregon populations formed a clade of closely related populations, a finding consistent with a recent introduction of stickleback into central Oregon. Finally, genome‐wide analysis of genetic diversity (π) and correlations of alleles within individuals in subpopulations ( F IS ) supported a role for introgressive hybridization in coastal populations and a recent expansion in central Oregon. Our results exhibit the power of next‐generation sequencing genomic approaches such as RAD ‐seq to identify both historical population structure and recent colonization history.